Influence of Sudden and Gradual Cooling Regimes on Strength, Near Surface Characteristics and Modulus of Elasticity of Polypropylene Fibre Reinforced Ternary Blended Concretes Subjected to Sustained Elevated Temperatures - Yaligar, Ashish A.; Vanakudre, Shrikant B. (AMC Indian Journal of Civil Engineering, 2018)
It is necessary to study the effect of sudden and gradual cooling regimes on M30 grade blended concrete when subjected to sustained elevated temperatures for three hours. The temperatures considered for the study are 30oC (RT), 100oC, 200oC, 300oC, 400oC, 500oC, 600oC, 700oC, 800oC, 900oC, and 1000oC. There is a comparison between conventional concrete and two ternary blended concretes (cement, fly ash, GGBFS and Cement, fly ash, silica fume) along with the inclusion of polypropylene fibre in each. After temperature test and cooling, concrete specimen was subjected to several strength and durability tests. As a result, all the specimens tested for gradual cooling regime shows better results than those tested for sudden cooling. Ternary blended concrete produced with cement, fly ash, silica fume along with polypropylene fibre combination shows better resistance against all temperatures compared to other two concretes.